2009
DOI: 10.1029/2008jf001078
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental record of debris flow initiation during natural rainfall: Implications for modeling slope stability

Abstract: [1] The middle of a hillslope hollow in the Oregon Coast Range failed and mobilized as a debris flow during heavy rainfall in November 1996. Automated pressure transducers recorded high spatial variability of pore water pressure within the area that mobilized as a debris flow, which initiated where local upward flow from bedrock developed into overlying colluvium. Postfailure observations of the bedrock surface exposed in the debris flow scar reveal a strong spatial correspondence between elevated piezometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
109
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 71 publications
(116 reference statements)
2
109
0
2
Order By: Relevance
“…For example, surface runoff or snowmelt may increase pore-water pressure/slope weight to initiate Coulomb slope failure. Intensive monitoring at a site in Oregon has revealed that hydrologically connected subsurface stormflow through a shallow bedrock zone can increase pore pressure, triggering landslides, in some instances, even in non-convergent topography (Montgomery et al, 2009). In this example, hydrological processes, via vertical and horizontal hydrological connectivity, are an important driver of sediment detachment (Duvert et al, 2011).…”
Section: Ii: Sediment Detachment Is Hydrologically Controlled; Sedimementioning
confidence: 99%
“…For example, surface runoff or snowmelt may increase pore-water pressure/slope weight to initiate Coulomb slope failure. Intensive monitoring at a site in Oregon has revealed that hydrologically connected subsurface stormflow through a shallow bedrock zone can increase pore pressure, triggering landslides, in some instances, even in non-convergent topography (Montgomery et al, 2009). In this example, hydrological processes, via vertical and horizontal hydrological connectivity, are an important driver of sediment detachment (Duvert et al, 2011).…”
Section: Ii: Sediment Detachment Is Hydrologically Controlled; Sedimementioning
confidence: 99%
“…require greater computational power and may still not represent the water flow processes adequately, such as the role of preferential flows and bedrock fracture systems in inducing conditions for failure (e.g Montgomery et al, 2009;Hencher, 2010;Beven, 2010;Beven and Germann, 2013). Even at sites where the costs of extensive field investigations can be justified, there is much that remains unknown about the subsurface including the detail of water flow pathways and knowledge of the hydro-mechanical behaviour of soils.…”
Section: Uncertainty Quantification In Landslide Hazard Estimationmentioning
confidence: 99%
“…Similarly, there is no consensus on the 15 level of soil moisture, i.e. the water volume stored in near-surface layers of the unsaturated substrate, required to trigger debris flows under different rainfall conditions (Johnson and Sitar, 1990;Montgomery et al, 2009). Essentially omitting the temporally variable yet cumulative influences of evaporation, transpiration and drainage on the soil wetness state, these concepts of antecedent wetness should be treated with caution and may hold only limited information.…”
mentioning
confidence: 99%
“…Johnson and Sitar, 1990;Coe et al, 2008;Montgomery et al, 2009) and other potentially relevant variables, such as canopy interception (e.g. Sidle and Ziegler, 2017), are typically not available at sufficient spatial and temporal resolutions.…”
mentioning
confidence: 99%